Implementación de un sistema de adquisición de datos de un proceso de secado de cacao y visualización de parámetros en HMI. - Cortez Vega, Willian Alexander (2021)
Today the development in electronics has motivated human society to seek ways to automate the home, industry, agriculture, transportation, etc. In this automation process, the microcontroller plays a very important role for the development of intelligent systems, the acquisition of data provides greater control to the processes of an organization and a faster response to the failures that may occur, the lack of these systems and the visualization of the parameters to be monitored causes that the products do not comply with the quality standards, also economic and time losses due to the lack of basic information for the analysis. This study consists of data collection, storage and monitoring in the internal chamber of six existing flat-plate solar panels, the system measures the temperature magnitudes by means of 66 sensors, the distribution of the devices are at the entrance, in the surface of the metal plate, in the middle and in the upper part where the glass is located, also a sensor will be located at the output of each of the modules this in order to have a precise measurement in the different sections, it is used a free software for the visualization of the parameters such as Unity, the data acquisition system will have the advantage of storing the parameters measured during the day, it will also have a meteorological station that will measure relative humidity, solar radiation and speed wind outside. The Xbee wireless communication system sends 7 seconds to the HMI due to the high number of data, this does not cause problems because in the SD memory, the stored data arrives every minute.